How We Elected Lincoln : Personal Recollections - Dittenhoefer, Abram J. (Abram Jesse), 1836-1919 (Book collections on Project MUSE., 2005)
In How We Elected Lincoln, originally published in 1916 and appearing now for the first time in paperback, we have the only firsthand account of Lincoln's political campaigns.